Gambaran lingkar perut, indeks massa tubuh dan kadar asam urat : - - Yasri, dwiyulia; Ramadhani, Khairini; Fasrini, Ulya Uti; Desmawati; Yusri, Elfira (Poltekkes Kemenkes Kupang, 2023)
Introduction: Increasing levels of uric acid (hyperuricemia) are associated with the incidence of obesity. Abdominal circumference and body mass index are commonly used indicators for obesity. This study aims to determine the description of abdominal circumference, body mass index, and uric acid levels in the staff of the Faculty of Medicine, Andalas University. Methods: This descriptive study used a cross-sectional design. A total of 41 research subjects from the secondary data obtained were staff at the Faculty of Medicine, Andalas University. The data consisted of age, sex, abdominal circumference, height, weight, and uric acid. The data was processed to see the frequency distribution of the research variables using univariate analysis. Results: The results of this study found that more than half of the research subjects were female, namely 28 (68.3%), and were in the age range of 26-45 years (65.9%). The study subjects who were categorized as central obesity and overweight were 65.85% and 73.17%, respectively. However, most of the research subjects had normal uric acid levels (82.93%).